Scout Extracurricular Activity Management at International Standard School (A Site Study at State-Owned Junior High School 3 Suruh, Semarang) - Retnowulan, Dwiningrum (2011)
The objectives of this research are to describe (1) the room design characteristic of the International Standard School Scout-Extra at State-Owned Junior High School of 3 Suruh, (2) the material characteristic of the International Standard School Scout-Extra at State-Owned Junior High School of 3 Suruh, (3) the characteristic of the scout extracurricular activity of the International Standard School at State-Owned Junior High School of 3 Suruh. Type of this research is qualitative and using ethnography. This research was conducted at State-Owned Junior High School of 3 Suruh. The main subjects were the principal, teachers and students of State-Owned Junior High School of 3 Suruh. Data collection method used interview, observation, and documentation. Data analysis started from (1) Data Collection, (2) data reduction, (3) data display, and (4) conclusion. Data validity test used credibility, transferability, conformability and dependability. The results of this research are (1) the room design of the scout extracurricular activity in State-Owned Junior High School of 3 Suruh is done by considering many things. The scout room in designed based on the activities that will be done, namely indoor room for the activities which do not need more movements and outdoor activities that need more movements. The principles used to design the room are the cleanliness, comfort, and simplify. Every scout activity room has been prepared a dustbin. The outdoor room is designed with the analysis of the possibility to make O, L, and U line formations. (2) The scout materials of the International Standard School in State-Owned Junior High School of 3 Suruh are delivered according to the content of the materials. . For the materials that contain a theory are given in the classroom, while for the materials that ask students to do practice will be given in outside of the classroom. The materials given include the basic competence of Scouting, the discipline, agility, survival, and also P3K (First Aid in an Accident). The speakers from outside the school are also invited to motivate the scout members of State-Owned Junior High School of 3 Suruh. (3) The scout extracurricular activity in the International Standard School of State-Owned Junior High School of 3 Suruh is done based on the existing provision. The activity is done every Saturday after the school end. The way to deliver the scout materials is using English, so it can train the scout members' ability in English. The method used is the among system with the principles are Ing ngarso sung tulodo, Ing madya mangun karsa, Tut wuri handayani. In the end of scouting activity, the school conducts an evaluation in the form of SKK and SKU tests.